Impact evaluation methods: Qualitative Methods - Wollenberg, Eva Karoline (2018)
Presentation by Lini Wollenberg, Low Emissions Development Leader, CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) at the Green Climate Fund Independent Evaluation Unit Learning-Oriented Real-Time Impact Assessment (LORTA) Program Inception Workshop July 24-26, 2018 Bangkok, Thailand